The Prevalence of Chronic Kidney Disease in Hypertensive Patients in Primary Care in Hong Kong: a Cross-Sectional Study - Xu, Shaowei; Li, Yim Chu; Chen, Catherine Xiaorui (Cardiology and Cardiovascular Medicine, 2022)
Background: To identify the prevalence of Chronic Kidney Disease (CKD) in Chinese hypertensive population managed in a local public primary care clinic and to explore its associated risk factors. Methods: Medical records of Chinese adult hypertensive patients (> 18 years of age) who had been followed up in a public General Outpatient Clinic (GOPC) from 1 Jan 2018 to 30 Jun 2018 were retrieved and reviewed, and a sample group was randomly selected. Demographic, clinical parameters including age, sex, smoking status, body weight, height, systolic and diastolic blood pressure, biochemical data, and comorbidities were collected from the Clinical Management System (CMS). Estimated glomerular filtration rate (eGFR) was calculated by using the Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) equation. CKD was defined as eGFR < 60 ml/min/1.73m2 and staged according to Kidney Disease Improving Global Outcomes (KDIGO) 2012 criteria. Student's t-test was used to analyze continuous variables and the Chi-squared test was used for categorical data. Multivariate Logistic regression was used to examine the association between CKD and variable associated factors. All statistical tests were two-sided, and a P-value of <0.05 was considered significant. Results: Among the 993 Chinese hypertensive patients included in the final analysis, 152 were found to have CKD, with overall prevalence being 15.3%. In addition, the prevalence of CKD increased with the ageing of the population. In multivariate analysis, associated factors for CKD included age (OR 3.6 for every 10 years increase), history of congestive heart failure (OR 6.3), diabetes mellitus (OR 1.7), gout (OR 3.0), low high-density lipoprotein cholesterol level (OR 0.29), and presence of proteinuria or albuminuria (OR 2.7). <p style="text-align:justi